Determination of alkaloid, saponin, phenolic and terpenoid presence in Euphorbiaceae and Burseraceae species - N., Liliwirianis; Musa, Nor Lailatul Wahidah; Daud, Shaari; Wan Mohd Zain, Wan Zuraida; Kassim, Jamaluddin; Yamani, Shaikh Abdul Karim (University Teknology MARA Pahang, 2011)
In a phytochemical survey carried out at UiTM Forest Reserve Jengka, Pahang, six species of Euphorbiaceae and four species of Burseraceae were collected and screened for alkaloid, terpenoid, saponin and phenolic. All the Euphorbiaceae species contain alkaloid, terpenoid, saponin and phenolic in different parts except the absence of phenolic content in Croton carcarilloide, Macaranga gigantean and Macaranga hypoleuca and absence of terpenoid in Agrotistachys longifolia. For the Burseraceae species all the samples studied contain saponin.